2016
DOI: 10.1177/0018720816634226
|View full text |Cite
|
Sign up to set email alerts
|

Taking Over Control From Highly Automated Vehicles in Complex Traffic Situations

Abstract: The present results can be used by developers of highly automated systems to appropriately design human-machine interfaces and to assess the driver's time budget for regaining control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
211
5
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(234 citation statements)
references
References 22 publications
15
211
5
3
Order By: Relevance
“…Our results showed that this process took less than 2 seconds, no matter in which emotional state drivers were. Recent studies comparing different types of NDRTs on takeover quality and timeliness showed that the types of NDRTs only influenced the takeover quality and not takeover time (Bueno et al, 2016;Gold et al, 2016;Körber et al, 2016;Zeeb et al, 2016;Zeeb, Härtel, Buchner, & Schrauf, 2017), providing further support for our findings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results showed that this process took less than 2 seconds, no matter in which emotional state drivers were. Recent studies comparing different types of NDRTs on takeover quality and timeliness showed that the types of NDRTs only influenced the takeover quality and not takeover time (Bueno et al, 2016;Gold et al, 2016;Körber et al, 2016;Zeeb et al, 2016;Zeeb, Härtel, Buchner, & Schrauf, 2017), providing further support for our findings.…”
Section: Discussionsupporting
confidence: 85%
“…In response to this known difficulty, research has been conducted to investigate factors affecting takeover performance, including the external driving environment (e.g., road elements, traffic situations, and weather conditions), types of NDRTs (e.g. reading, typing), individual characteristics (e.g., training, prior experience with automation, trust in automation, age), and design of human-machine interface (e.g., multi-modal display) (Eriksson & Stanton, 2017;Gold et al, 2016;Helldin, Falkman, Riveiro, & Davidsson, 2013;Wan & Wu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research focused on the take-over situation, in which drivers have to take over the DDT after a period of automated driving. Results revealed an influence of traffic density (Radlmayr, Gold, Lorenz, Farid, & Bengler, 2014), (Gold, Körber, Lechner, & Bengler, 2016) or automation duration (Feldhütter, Gold, Schneider, & Bengler, 2017) on take-over performance. In addition, individual differences (Körber & Bengler, 2014) and NDRTs were analyzed (Merat, Jamson, Lai, & Carsten, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…In an autonomous system, however, the user is not involved directly with the control of the vehicle, which presents questions of whether sobriety and attentiveness are required by the users. In fact, it is just as likely that users of HAVs might want to totally disengage from the driving process and instead focus on some other activity (e.g., answering email, working, sleeping, reading, watching a film, or engaging in some other forms of entertainment) (Gold & Bengler, ). These things may seem out of reach at present but, if HAVs operate as promised, there is no transportation safety‐centric reason to believe that individuals should not be engaged in any of these activities.…”
Section: The Case Of Autonomous Vehiclesmentioning
confidence: 99%